Perceptions of lifestyle-related risk communication in patients with breast and colorectal cancer: a qualitative interview study in Sweden - Åsa Grauman; Erica Sundell; Jennifer Viberg Johansson; Nina Cavalli-Björkman; Jessica Nihlén Fahlquist; Mariann Hedström (BMC, 2024)
Abstract Background Informing individuals about their risk of cancer can sometimes have negative consequences, such as inflicting unnecessary worry and fostering stigma. This study aims to explore how patients diagnosed with breast or colorectal cancer perceive and experience risk communication, particularly concerning the increased focus on lifestyle behaviors as the cause of cancer. Methods Semi-structured interviews were conducted during autumn 2023, with 23 Swedish individuals, aged 34 to 79 years, diagnosed with breast or colorectal cancer. The collected data were analyzed using inductive thematic analysis described by Braun & Clark. The study adopted an experiential orientation grounded in critical realism. Results Five themes with ten sub-themes were identified: Thoughts and feelings about the causes of cancer, Moralizing messages and negative encounters, The need to take action, Balancing uncertain risks and a fulfilling life, and Societal benefits of risk communication. The participants expressed that knowledge of the the cause of cancer is closely related to the possibility of taking preventive action against relapses. Ability to take action was also perceived important for their well-being. Therefore, risk information entails both feelings of self-blame and hope for the future. Participants asked for both information and lifestyle support from healthcare professionals. Lifestyle interventions and patient support groups were solicited and perceived as an important aspect of cancer survivals' well-being, and may help to reduce the cancer-related stigma. Conclusion Individuals that have or have had breast or colorectal cancer, including those leading healthy lifestyles, found moralistic risk information offensive, leading to feelings of shame when thinking about other peoples thoughts. Balancing information involves providing transparent, evidence-based information while considering individual and social contexts, avoiding stigmatization and blame, and supplementing information with support.